Probiotic Characteristics of Bifidobacterium Spp. by in Vitro Assessment - Vengrasalam, Kalaivaani (1996)
Probiotics are organisms which are natural gut isolates and used as dietary adjuncts that is believed to benefit man and animals. An organism to be selected as a probiotic should posses certain important characteristics. This project was designed to screen bifidobacterial strains to be used as dairy starter cultures. Few in vitro methodologies were selected for the above purpose. Eighteen strains of bifidobacteria were obtained from ATCC. Firstly characterization of the strains were carried out. All strains were gram positive rods of variable sizes with bifurcated Y and V forms, catalase negative and did not grow aerobically . Almost all the strains fermented glucose, fructose, galactose and lactose except few strains from honey bees did not ferment galactose and lactose. The fermentation characteristics of other sugars were comparable to previous reports on bifidobacteria. Most of the bifidobacteria strains tested were resistant to aminoglycosides, nalidixic acid, polymyxin B, colistin and sulfonamides. Tetracyclines, moxalactam, furazolidone,nitrofurazone, cloxacillin and fusidic acid showed variable effectiveness. Bacitracin, erythromycin, oleandomycin, chloramphenicol, imipenam, nitrofurazone, penicillin, ampicillin, amoxicillin, carbenicillin and novobiocin were very inhibitory. Almost all the strains produced more or equal amount of acetic acid than lactic acid in the fermentation end product. The strain designated B. adolescentis (ATCC 1 1 146) did not show the characteristics of bifidobacteria. The survival of bifidobacteria in low pH showed wide strain variation. B. bifidum (ATCC 3591 4), B. breve (ATCC 1 5698), and B. in/antis (ATCC 27920) possess excellent acid tolerance followed by B. adolescentis (11146, 15705, and 15706). Growth in bile also showed strain variation. B. longum (ATCC 15707) had the best bile tolerance followed by B. longum (ATCC 15708). The others that showed good bile tolerance were B. adolescentis (ATCC 11146), B. asteroides (ATCC 25909 and 25910), and B. breve (ATCC 1 5700) followed by B. indicum (ATCC 25913) and B. bifidum (ATCC 35914). The double layered assay used to study the antibacterial activity of bifidobacteria against other organisms was found to be suitable to screen bifidobacteria strain for bacteriocin production. Bifidobacterium spp. inhibited Pseudomonas aeruginosa, Bacillus megaterium, B. licheniforms, B. subtilis, B. sphaericus, E. coli, L. monocytogenes and S. enteritidis in vitro. The inhibition was confirmed as due to the production of organic acids. The tested strains did not produce other inhibitory substances. The strains that possess the best inhibition activity include B. adolescentis (ATCC 15705), B.